A família Myrtaceae na Floresta Nacional de Ipanema, Iperó, São Paulo, Brasil - Silva, Alan Teixeira da (2014)
With about 1.000 species and 23 genera occurring in Brazil, Myrtaceae is one of the most important families in floristic surveys, mainly in Cerrado and Atlantic Forest areas. The National Forest of Ipanema is occupied mostly by Atlantic Forest and small areas of Cerrado; it is also possible to observe signs of human exploration in the past in the area. The main objective of this work is to improve the knowledge of Myrtaceae in the National Forest of Ipanema. For this, field trips were made between September 2012 and March 2013 and the collections of the following herbaria were analyzed: CCTS, ESA, IAC, SP, SPSF, UEC. After data analysis 23 species of Myrtaceae and 6 genera were found: Eugenia (10 species), Myrcia (4 species), Psidium (4 species), Campomanesia (3 species), Calyptranthes (1 species) and Plinia (1 species). Descriptions, illustrations, maps of geographical distribution and keys of identification of the species were prepared. After data analyzis C. neriiflora was identified in the IUCN red list of threatened species as vulnerable risk, by the other side, Psidium guajava occurs at high frequency, as it is an invasive species, it could endanger the local biodiversity. All the collected specimens were deposited in CCTS collection.